Engineering of lysin by fusion of antimicrobial peptide (cecropin A) enhances its antibacterial properties against multidrug-resistant Acinetobacter baumannii - Islam, Md Maidul; Kim, Dooyoung; Kim, Kyeongmin; Park, Su-Jin; Akter, Samia; Kim, Jeongah; Bang, Seunghyeok; Kim, Shukho; Kim, Jungmin; Lee, Je Chul; Hong, Chang-Won; Shin, Minsang (Frontiers in Microbiology, 2022)
Most clinical isolates of Acinetobacter baumannii, a nosocomial pathogen, are multidrug-resistant (MDR), fueling the search for alternative therapies. Bacteriophage-derived endolysins have potent antibacterial activities and are considered as alternatives to antibiotics against A. baumannii infection. Gram-negative bacteria possess an outer peptidoglycan layer that prevents direct contact between the endolysin and the cell wall. We hypothesized that the fusion of antimicrobial peptide (AMP) with endolysin could help reduce endolysin tolerance, subsequently increasing bactericidal activity through membrane permeabilization. Accordingly, we fused cecropin A, a commonly used AMP, with the N-terminus of AbEndolysin, which enhances the bactericidal activity of the chimeric endolysin. The bactericidal activity of cecropin A-fused AbEndolysin increased by at least 2–4 log-fold for various MDR clinical A. baumannii strains. The in vitro bactericidal activity results also showed higher bacterial lysis by the chimeric endolysin than that by the parental lysin. The engineered AbEndolysin (eAbEndolysin) showed synergistic effects with the beta-lactam antibiotics cefotaxime, ceftazidime, and aztreonam, and an additive effect with meropenem and imipenem. eAbEndolysin had no cytotoxic effect on A549 cell line and rescued mice (40% survival rate) from systemic A. baumannii infection. Together, these findings suggest the potential of lysin therapy and may prompt its use as an alternative to antibiotics.